Akulturasi Budaya Bangunan Masjid Tua Cirebon Studi pada Masjid Kaliwulu, Plered - Hakim, Abdul (SUHUF, 2011)
Cirebon’s role as an early centre for the dissemination of Islam is evident in its numerous archeological remains and ancient buildings, including old mosques. The architectural details of these mosques may reflect the values of the culture in which they were created. One such old mosque is the Kaliwulu Mosque, in Plered, Cirebon. This article attempts to examine the layers of acculturation evident in this mosque through an examination of its architecture, the layout of interior space, and decorative details.